2020
DOI: 10.2196/18080
|View full text |Cite
|
Sign up to set email alerts
|

Intention to use Medical Apps Among Older Adults in the Netherlands: Cross-Sectional Study

Abstract: Background The increasing health service demand driven by the aging of the global population calls for the development of modes of health service delivery that are less human resource–intensive. Electronic health (eHealth) and medical apps are expected to play an important role in this development. Although evidence shows mobile medical apps might be effective in improving the care, self-management, self-efficacy, health-related behavior, and medication adherence of older adults, little is known ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 47 publications
6
49
1
Order By: Relevance
“…Financial costs directed to patients or informal caregivers might be an obstacle to using the eHealth service or application or continuation of usage of these services, especially in countries where mandatory health insurance coverage is lacking. Although a recent study in the Netherlands identified finance as a factor not significantly related to intention to use medical apps among older persons [ 77 ], future studies should focus on how the costs are covered and who should pay for the direct or indirect costs of eHealth.…”
Section: Discussionmentioning
confidence: 99%
“…Financial costs directed to patients or informal caregivers might be an obstacle to using the eHealth service or application or continuation of usage of these services, especially in countries where mandatory health insurance coverage is lacking. Although a recent study in the Netherlands identified finance as a factor not significantly related to intention to use medical apps among older persons [ 77 ], future studies should focus on how the costs are covered and who should pay for the direct or indirect costs of eHealth.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this study, we selected behavioral intention to use mHealth applications from TAM as an outcome of interest. Building on the work of Askari et al [ 29 ], the statements operationalizing intention to use are taken from Venkatesh and Davis [ 44 ] and translated into Dutch, adding one new statement to account for linguistic differences.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, however, older adults are less likely to adopt new technologies such as mHealth [24][25][26][27][28]. Before the pandemic, almost 50% of Dutch older adults had no intention to use mHealth applications [29].…”
Section: Introductionmentioning
confidence: 99%
“…Positive attitudes are associated with an increased likelihood of behaviour and behavioural intentions (Davis, 1989;Fishbein & Ajzen, 1975;McEachan, Conner, Taylor, & Lawton, 2011;Rosenstock, Strecher, & Becker, 1988). Such as in the case of DI, people with more favourable attitudes to DI are more likely to have positive intentions to use DI, and this is supported by research (Askari, 2020;Patel et al, 2020;Wangberg, Gammon, & Spitznogle, 2007). Therefore, people's attitudes are crucial to understanding people's readiness to engage with DI.…”
Section: Introductionmentioning
confidence: 97%